Management tools for the implementation of ESG principles in an industrial company - I. V. Groshev; T. M. Gololobova (Управление)
The purpose of the work is to analyse the tools used in the process of implementing ESG principles (environmental, social, governance) on the example of an industrial company. The task that has been solved by the authors of the study is to assess the ESG policy, which has recently become a priority for the development of industrial enterprises in modern economic conditions. To solve this problem, the methodology of an integrated approach and system analysis is used, which is the basis of the study. The publications of Russian research[1]ers devoted to the problems of sustainable development in the new Russian conditions in the sectoral spheres of the domestic economy, fruitfully developed by the Russian Union of Industrialists and Entrepreneurs, are the theoretical basis that has allowed us to identify effective management tools for the implementation and realisation of the ESG principles. Within the framework of the toolkit, the project roadmap, mechanism for setting and completing key tasks and terms of reference аre separately highlighted. As a result, the proposed management algorithm has been evaluated and its main components have been presented, which are becoming a priority at the present stage of the development of the Russian economy. The obtained research results can be used in the elaboration of directions of the industrial sector of Russia as well as in the elaboration of the strategic development of the innovative potential of companies and enterprises of the industrial complex.